The Effect Of Location For On-Site Detention (OSD) On Peak Attenuation Using Stormwater Management Model - Puzi, Nurul Fathiha Mohd (Universiti Sains Malaysia, 2017)
The objective of this study is to evaluate the flow attenuation of the urban development by using SWMM modelling. The project is aimed on the modelling of the drainage system in urban area using SWMM model, to evaluate storm with different duration and flow attenuation of the development area. The drainage system is an essential part of living in urban area, as it reduces the flooding by conveying water away. The concept of “control at source” or “Best Management Practices (BMPs)” were introduced to prevent flooding from happened. Therefore, a new manual was introduced to manage the drainage system to be more efficient which is “Manual Saliran Mesra Alam” (MSMA). Stormwater Management Model (SWMM) is widely used for planning, analysis and design related to urban storm water runoff, combined sewers, sanitary sewers, and other drainage systems in urban areas, with many applications in non-urban areas as well. The system is important in modelling especially in determination of drain size to reduce flooding and it is also can be modelled to determine the detention facilities that can reduce the flood and improve the quality of stormwater. Over this study, the total rainfall of 10 years ARI for 15 minutes is 193 mm/hr and for 30 minutes is 127 mm/hr. From the calculation based on MSMA the volume of each tank in case 1 is 216m3(4 tanks), case 2 is 480m3(2 tanks), and case 3 is 875m3(1 tank). In addition, from the analysis of case 1 shows the higher percentage of attenuation which is approximately 30% compared to case 2 and case 3 for both storm duration of 15 minutes and 30 minutes.